Leaf Phenological Stages of Winter Oilseed Rape (Brassica napus L.) Have Conserved Photosynthetic Efficiencies but Contrasted Intrinsic Water Use Efficiencies at High Light Intensities - Dellero, Younès; Jossier, Mathieu; Bouchereau, Alain; Hodges, Michael; Leport, Laurent (Frontiers in Plant Science, 2021)
Leaf senescence in source leaves leads to the active degradation of chloroplast components (photosystems, chlorophylls, ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco)) and plays a key role in the efficient remobilization of nutrients towards sink tissues. However, the progression of leaf senescence can differentially modify the photosynthetic properties of source leaves depending on plant species. In this study, the photosynthetic and respiratory properties of four leaf ranks of oilseed rape describing leaf phenological stages having different sink-source activities were analysed. To achieve this, photosynthetic pigments, total soluble proteins, Rubisco amounts and the light response of chlorophyll fluorescence parameters coupled to leaf gas exchanges and leaf water content were measured. Photosynthetic CO2 assimilation and electron transfer rates, Rubisco and chlorophyll levels per leaf area were gradually decreased between young, mature and senescent leaves but they remained highly correlated at saturating light intensities. However, senescent leaves of oilseed rape had a lower intrinsic water use efficiency compared to young and mature leaves at saturating light intensities that was mainly due to higher stomatal conductance and transpiration rate with respect to stomatal density and net CO2 assimilation. The results are in favour of a concerted degradation of chloroplast components but a contrasted regulation of water status between leaves of different phenological stages of winter oilseed rape.